SPECIFICS OF HEART RATE VARIABILITY AND PARAMETERS OF ELECTROENCEPHALOGRAPHY IN PATIENTS WITH ARTERIAL HYPERTENSION - M. Kh. Kurdanova; M. A. Umetov; I. A. Beslaneev; L. M. Batyrbekova; Kh. A. Kurdanov (Кардиоваскулярная терапия и профилактика)
Aim. Investigation of heart rate variability parameters (HRV), α- & β-rhythms of electroencephalography (EEG) and their interrelations in patients with arterial hypertension (AH).Material and methods. Totally 55 persons studied at the age 35-64 y.o. – 35 pts. with AH 2 stage and 20 healthy volunteers. All patients underwent clinical examination, including HRV and EEG. The HRVs were determined in frequency field of shared specter (SS) — VLF, LF, HF and static values – dynamic digits SDNN, SDANN and CV etc. EEG was done at 21-lead pattern with mono- and bipolar electrodes. The data obtained was processed by the parametric and nonparametric statistics software.Results. HRV parameters — SS, VLF, LF and SNDD were significantly decreased in the group of AH patients. Among HRV parameters (TP, VLF, LF, HF) and frequency and amplitude EEG values were found correlational linkages more prominent in AH patients.Conclusion. The data obtained witnesses close interconnections and relationships of HRV, bioelectricity of the brain and hemodynamic in patients with AH.